ANALISIS MUTU ORGANOLEPTIK DAN MUTU KIMIA PIA BLACKPINK DENGAN PENAMBAHAN KULIT BUAH NAGA MERAH (HYLOCEREUS POLYRHIZUS) - Febry K.D, Ayu Bulan; Amalia, Mutia Reski; Hadi, Novian Swasono; Setiawan, Denny Indra; Nuryani, Nuryani; R Ahmad, Rodiyatan Mardiyah (JOURNAL HEALTH AND NUTRITIONS, 2025)
Pia is a traditional delicacy from Gorontalo that has been innovatively developed through the addition of red dragon fruit peel as a natural coloring agent and antioxidant source. This innovation aims to enhance the nutritional value and visual appeal of the product while utilizing dragon fruit peel waste, which is rich in anthocyanins. Objective of study was analyzed the organoleptic qualities (taste, color, aroma, and texture) and chemical composition of pia blackpink supplemented with 50 g, 60 g, 70 g, and 80 g of red dragon fruit peel. The methods of study was an experimental study employed a Completely Randomized Design (CRD) with four treatment levels and four replications. A total of 30 semi-trained panelists participated in the organoleptic evaluation. Proximate analysis was conducted to determine the content of protein, fat, carbohydrates, fiber, moisture, ash, and vitamin C. Results revealed that addition of red dragon fruit peel significantly improved organoleptic qualities, with the best results observed in the 80g treatment group (P4). The chemical composition of this variant included protein (8.12%), fat (5.20%), carbohydrates (72.58%), fiber (0.91%), moisture (13.24%), ash (0.86%), and vitamin C (225 mg/1000 g). The conclusion of the study was addition of red dragon fruit peel enhances both the sensory attributes and nutritional quality of pia, making it more appealing and beneficial to consumers. Pia adalah makanan khas Gorontalo yang dikembangkan dengan inovasi penambahan kulit buah naga merah sebagai pewarna alami sekaligus sumber antioksidan. Inovasi ini bertujuan meningkatkan nilai gizi dan daya tarik produk, sekaligus memanfaatkan limbah kulit buah naga yang kaya antosianin. Tujuan penelitian untuk menganalisis mutu organoleptik (rasa, warna, aroma, dan tekstur) serta kandungan kimia pia blackpink yang diberi tambahan kulit buah naga merah sebanyak 50 g, 60 g, 70 g, dan 80 g. Metode penelitian yang digunakan adalah eksperimen, menggunakan Rancangan Acak Lengkap (RAL) dengan empat perlakuan dan empat replikasi, serta melibatkan 30 panelis agak terlatih dalam uji organoleptik. Uji kimia menggunakan analisis proksimat untuk mengetahui kadar protein, lemak, karbohidrat, serat, air, abu dan vitamin C. Hasil penelitian menunjukkan bahwa penambahan kulit buah naga merah secara signifikan meningkatkan mutu organoleptik, dengan hasil terbaik pada penambahan 80 g (P4). Komposisi kimia pia tersebut meliputi protein 8,12%, lemak 5,20%, karbohidrat 72,58%, serat 0,91%, air 13,24%, abu 0,86%, dan vitamin C 225 mg/1000 g. Kesimpulan menunjukkan penambahan kulit buah naga tidak hanya meningkatkan rasa dan penampilan pia, tetapi juga menjadikannya lebih bergizi dan menarik bagi konsumen.